THE EFFECT OF STORY METHODS WITH OBJECTS AROUND TO THE INDEPENDENCE OF CHILDREN - Siti Indatul Laili; Ariu Dewi Yanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Children's independence can be seen from the ability of children to think and do for themselves so that children are not dependent on others. Building children's independence is easier to do early on and done in a fun way such as telling a story that is recognized by the child for example by using things around. The purpose of this study is to prove the effectiveness of the story method with items around the child's independence. This research design uses one group pre-post test design. The population of this research is all 80 children of RA Mu'awanah Al-Hasyimiyah Jombang. The sample of this study were all children of RA Mu'awanah Al-Hasyimiyah Jombang with 80 respondents taken by total sampling. The measuring instrument used was a questionnaire to assess the independence of children with 100% valid and reliable test results with ρ = 0.982. Research time September 2019. Statistik test using the Wilcoxon Sign Rank test with label table = 0.05. The results showed that respondents who had positive independence from 38 (47.5%) respondents increased to 71 (88.75%) of respondents after being given a story on the topic of using things around such as shoes, sandals, clothes, toys, stationery. Wilcoxon Sign Test results Rank ρcount 0,000 = and label table = 0.05. This means that there is an influence of the story method with items around the child's independence. Stories with things around that are already known and are familiar with the child even every day used by the child can reflect independent behavior so that the child can do something without help from others, able to make choices and take responsibility for his choices.